Preoperative TNF-a Reduction in Endometriosis Lesions with Combined Oral Contraceptives - Thengkano, Irwanto; Yanuari Primariawan, Relly; Hernaningsih, Yetti; Ratna Dwiningsih, Sri (Indonesian Journal of Obstetrics and Gynecology, 2025)
Background: The goals of endometriosis treatment vary greatly depending on the patient's symptoms and reproductive needs. Hormonal therapy to alleviate pain has generally been shown to have positive effects. Combined Oral Contraceptives (COC) are widely available, relatively affordable, and well-known by the public. Objective: This study aims to compare the effects of COC therapy with two newer endometriosis treatments: oral Dienogest 2 mg and injectable Leuprorelin acetate 3.75 mg on TNF alfa levels in serum and peritoneal fluid. Methods: Forty subjects were divided into four groups: three groups receiving medical therapy—COC (0.03 mg ethinylestradiol and 0.15 mg levonorgestrel, taken one active tablet per day continuously), oral Dienogest 2 mg, and intramuscular Leuprorelin acetate 3.75 mg every four weeks—and a control group of endometriosis patients who had not received any hormonal therapy. Peripheral venous blood samples were taken before surgery, and peritoneal fluid was collected at the start of surgery in the pelvic cavity. TNF alfa levels were analyzed using the ELISA method. Data analysis was performed using the Kruskal-Wallis test with a significance level of 0.05. Results: The Kruskal-Wallis test showed significant differences between treatment groups in TNF alfalevels in peritoneal fluid (p:0.023), specifically between the COC group and the control group, and between the Dienogest group and the control group. Conclusion: Preoperative hormonal therapy for estradiol suppression provides limited benefit in reducing systemic inflammatory agents but is effective locally, as evidenced by reduced TNF alfa levels in the peritoneal fluid after preoperative COC and Dienogest therapy. Keywords: COC, Dienogest, Leuprorelin Acetate, Serum, Peritoneal Fluid, TNF alfa